PENDAMPINGAN PENERAPAN PENCATATAN AKUNTANSI SEDERHANA DAN PELAPORAN KEUANGAN AWAL MENGGUNAKAN TEMAN BISNIS UNTUK KEPATUHAN SAK EMKM DI KECAMATAN MANTRIJERON, KOTA YOGYAKARTA - Ananda Marizka Dwi Pertamasari; Hasim As’ari (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service aims to assist MSMEs "Penyetan Selera Pedas" and "Molen Bu Yati" in Mantrijeron District in implementing digital-based simple accounting records for SAK EMKM compliance. The primary problems faced by partners are manual, unstructured financial management and the mixing of personal and business funds. Methods used include observation, interviews, socialization of accounting principles, and intensive training on the "Teman Bisnis" application. Results show a significant increase in the regularity of daily transaction recording and the partners' ability to prepare initial financial reports digitally. The transformation from manual to digital systems helps business owners understand financial conditions in real-time. This assistance is crucial as a foundation for MSMEs to enhance accountability and expand access to capital in the future.